Occurrence and Antibiogram of Non-Sorbitol Fermenting Escherichia coli in Marketed Raw Meat of Dharan, Eastern Nepal - Ghimire, Santoshi; Thapa, Devendra; Ghimire, Arjun; Subba, Prince; Sah, Shiv Nandan (Tribhuvan University Journal of Food Science and Technology, 2022)
This study aimed to explore the distribution of non-sorbitol fermenting Escherichia coli (E. coli) from meat marketed in Dharan city and study its susceptibility to antibiotics. This study was the laboratory based cross-sectional study conducted from December 2016 to May 2017 at Microbiology laboratory of Central Campus of Technology. A total of 24 meat samples from butcher’s retail shop of Dharan were taken for study that included 6 chickens, 6 buffalo, 6 pork, and 6 goat meat sample. The bacterial isolates from meat samples were isolated by routine microbiological procedures and identified by colony characteristics on selective medium, Gram's staining and biochemical tests. The antibiotic susceptibility test (AST) of the isolated bacteria was performed by Kirby–Bauer disc diffusion method. Results reported 41.66% (10/24) prevalence of non-sorbitol fermenting E. coli in meat samples. However, this distribution was not statistically significant (p=0.877). The prevalence of E. coli was 3 (50%) in chicken, 3 (50%) in buffalo, 2 (33.33%) in pork and 2 (33.33%) in goat meat. All the isolated E. coli were subjected to the antibiotic susceptibility test using 17 different antibiotics and all the strains showed 100% resistance against ampicillin, amoxicillin and ceftazidime and the highest sensitivity towards gentamycin (90%), ceftriaxone (80%), amikacin (80%) and chloramphenicol (80%). The 100% multidrug resistance was observed in all the isolates. This study concludes that the meat consumers of Dharan are at higher risk of infection by pathogenic strain of E. coli. The increasing incidence of multi drug resistance of pathogenic strains may pose serious health ailment among semi-processed meat consumers whilst the cooked meat consumers too are at risk of toxin-mediated food poisoning.